ICT FOR ARABIC LEARNING: A BLENDED LEARNING IN ISTIMA’ II - Mufidah, Nuril; Isyaty, Irtahat; Kholis, Nur; Bin Tahir, Saidna Zulfiqar (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2018)
Listening skills (maharah istima’) are the initial abilities that a person must master in learning Arabic. However, due to the lack of attention to Maharah Istima's learning, which was caused by a lack of variation in learning, a teacher / lecturer must be able to innovate in teaching. One form of innovation is to use video media to teach special materials. This study aims to describe the use of Information and Communications Technology (ICT) as a blended learning in Maharah Istima’ II lectures as well as the perception of Arabic Language Department (PBA) students of Maulana Malik Ibrahim Malang State Islamic University 2016/2017. This research is a qualitative research with data collection methods by observation and interviews. The results showed that ICT in maharah istima learning could improve student learning motivation. In addition it can help students add new vocabulary and can be applied in speaking skills (maharah kalam).